Robust oxygen excess ratio control of PEMFC systems using adaptive dynamic programming - Jing Zhu; Peng Zhang; Xiang Li; Bin Jiang (Energy Reports, 2022)
To improve the power generation efficiency and cells lifetime of proton exchange membrane fuel cells, the oxygen excess ratio (OER) control problem is investigated in this paper. With the use of the double-loop cascade control structure, our work reinforces the iteration adaptive dynamic programming (ADP) algorithm and develops a robust OER control strategy drawing upon rich tools and techniques in sliding mode control theory. Our contribution is threefold. First, the proposed OER control policy is insensitive to various dynamics and disturbances by using refined super-twisting sliding mode controller in the external control loop. Second, the ADP-based controller is employed in the internal control loop to approximate the real optimal tracking control policy. The algorithm is computationally efficient and easy to implement in hardware platforms. Third, simulation results show that the proposed OER control strategy has a quick, smooth response, which can be further refined by means of numerous advanced neural network algorithms.